KOMPETENSI MENGAJAR MAHASISWA PPL PRODI PENDIDIKAN JASMANI FKIP UNTAN TA 2019/ 2020 KOTA PONTIANAK - Priyadi, Retno; Simanjuntak, Victor G; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Abstract The problem in this study is how to teach competence students practice field experience physical education study programs 2019/2020 in junior high school and high school at Pontianak city. This research is a quantitative study with survey method. Data collection techniques by giving questionnaires. The population in this study was 39 schools. Data analysis using a percentage. Based on the results of research that has been done, the result obtained that the teaching competencies of students in the field study program practice physical education 2019/2020 in junior and high school at Pontianak city have 3 categories. First, category is a very good category with a percentage of 89,74%. The second category is a good category is 7,69%. The third category is 2,56% good enough. While students in bad catagories do not exist. This means competence students practice field experience in secondary and middle schools senior high school in Pontianak are classified as good. Keywords : Physical Education, Survey, Teaching Skill